Normal cavum veli interpositi at 14–17 gestational weeks: three‐dimensional and Doppler transvaginal neurosonographic study. (1st July 2021) - Birnbaum, R.; Barzilay, R.; Brusilov, M.; Wolman, I.; Malinger, G.
ABSTRACT: Objectives: To provide evidence to support the hypothesis that the midline cyst‐like fluid collection that is frequently observed on fetal brain ultrasound (US) imaging during the early second trimester represents a normal transient cavum veli interpositi (CVI). Methods: This was a retrospective analysis of 89 three‐dimensional normal fetal brain volumes, acquired by transvaginal US imaging in 87 pregnant women between 14 and 17 gestational weeks. The midsagittal view was studied using multiplanar imaging, and the maximum length of the fluid collection located over (dorsal to) the tela choroidea of the third ventricle was measured. We calculated the correlation of the transverse cerebellar diameter (TCD) and of the maximum length of the fluid collection with gestational age according to last menstrual period. Color Doppler images were analyzed to determine the location of the internal cerebral veins with respect to the location of the fluid collection. Reports of the second‐trimester anatomy scan at 22–24 weeks were also reviewed. Results: Interhemispheric fluid collections of various sizes were found in 55% (49/89) of the volumes (mean length, 5 (range, 3.0–7.8) mm). There was a strong correlation between TCD and gestational age (Pearson's correlation, 0.862; P  < 0.001). There was no correlation between maximum fluid length and gestational age (Pearson's correlation, –0.442; P  = 0.773). Color Doppler images were retrieved in 32 of the 49 fetuses; in 100% of these, the internal cerebral veins coursed within the echogenic roof of the third ventricle. The midline structures were normal at the 22–24‐week scan in all cases. Conclusions: In approximately half of normal fetuses, during the evolution of the midline structures of the brain, various degrees of fluid accumulate transiently in the velum interpositum, giving rise to a physiologic CVI. Patients should be reassured that this is a normal phenomenon in the early second trimester that, if an isolated finding, has no influence on fetal brain development. © 2020 International Society of Ultrasound in Obstetrics and Gynecology